Factors associated with psychological and physical domestic violence against Peruvian adolescents from an ecological approach - Cahui Ramírez, Claudia Rebeca (2022)
Objective: To estimate the factors associated with psychological and physical domestic violence against Peruvian adolescents considering the ecological model of violence. Materials and methods: A cross-sectional study based on a secondary analysis of the 2015 National Survey on Social Relations (ENARES) database. A three-stage stratified cluster sampling was conducted with 1,500 adolescents. The main variables were physical and psychological violence. The associated variables were also analyzed following the ecological model and using logistic regression for determining odds ratios (OR) and 95 % confidence intervals (95 % CI). Results: From among the surveyed adolescents, 23.73 % experienced severe psychological violence and 42.47 % severe physical violence. Men were less exposed to psychological violence (OR = 0.60; 95 % CI: 0.41 – 0.86) compared to women. Witnessing constant fights between parents always or almost always exposed adolescents to physical violence, as opposed to those who almost never experienced parental fighting (OR = 5.80; 95 % CI: 2.47 – 13.60). Those who assumed that disobeying their parents was a reason for physical violence were exposed to it almost twice (OR = 1.27; 95 % CI: 1.01 – 1.59) as much as those who did not think that way. Conclusions: Regarding life experience, the younger the adolescent, the more prone to physical violence. Additionally, being a woman increases the probability of receiving psychological abuse. In the national context, physical violence may be considered an acceptable behavior by a large part of the population. Moreover, the younger the abused adolescents are, together with their incapacity to protect themselves, the worse this behavior pattern could be.